MEASURING INTERACTIVE SERVICE QUALITY: SOME OPPORTUNITIES FOR FURTHER STUDY - Agung Sutrisno (Jurnal Tekno Mesin, 2018)
Service quality is very important to improve competitive advantage of industrial organizations. This paperpresents a summary on some research gaps within current service quality measurement models and explores thepossibility to extend study on interactive service quality arena. The content of the paper is commenced byliterature review to manuscripts related to service quality measurement models, interactive service quality, someobservable gaps on interactive service quality measurement models.At conclusion, some directions for furtherstudies are presented.Keywords: Service Quality, Interactive, Bi-directional Relationship, Behavior Modeling, Taguchi Loss Function.